Influence of work hours and commute time on food practices: a longitudinal analysis of the Household, Income and Labour Dynamics in Australia Survey - Oostenbach, Laura Helena; Lamb, Karen Elaine; Crawford, David; Thornton, Lukar (My University, 2022)
Work hours and commute time are key contributors to time scarcity, with potential detrimental implications for healthy eating. This study examined (1) associations between work and commute hours with food practices and (2) within-individual associations between changes in work and commute hours with changes in food practices. Longitudinal study SETTING: Australia PARTICIPANTS: Data were from 14 807 respondents in waves 7 (2007), 9 (2009), 13 (2013) and 17 (2017) of the Household, Income and Labour Dynamics in Australia Survey. The sample for this analysis included individuals who were in paid employment in at least one of the four waves. Outcomes included frequency of out-of-home food purchasing for breakfast, lunch, dinner and all three summed eating occasions, and fruit and vegetables consumption. Results indicated the longer individuals spent working and commuting, the more likely they were to purchase out-of-home foods (frequency of total out-of-home food purchasing: incidence rate ratio (IRR)=1.007 (95% CI 1.007 to 1.008)), and the less they consumed fruit and vegetables, although reductions in fruit and vegetables servings were minimal (fruit: β=-0.002 (95% CI -0.003 to -0.001), vegetables: β=-0.002 (95% CI -0.003 to -0.001)). Similar results regarding associations with out-of-home food purchasing were observed when examining within-individual changes (IRR=1.006 (95% CI 1.005 to 1.007)). Results suggest employment-related time demands push towards more frequent out-of-home food purchasing. In the long term, this may have negative health consequences as out-of-home foods tend to be less healthy than home-prepared foods.
BMJ Open
Keywords: Health and wellbeing; Lifestyle